2007
DOI: 10.1016/j.jcrs.2007.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and visual impact of postoperative refractive error after cataract surgery in rural China

Abstract: Accurate selection of postoperative refractive error was achieved by local surgeons in this rural area. Based on visual function results, aiming for mild postoperative myopia may not be suitable in this setting. Implanting average-power IOLs significantly reduced postoperative presenting vision, but not visual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…20 The decrement in visual function reported by children with Ն Ϫ3.5 to Ͻ Ϫ2.5 D of myopia compared with those with refractive error Ն Ϫ0.5 D was 16.2 points, which exceeds the difference in self-reported visual function between persons with postoperative vision above and below 6/60 in the surgical eye in the above-cited study. This very significant impact of refractive error on self-reported visual function is consistent with our recent report of significant improvement in visual function with provision of spectacles among school-aged children having modest levels of refractive error in rural Mexico.…”
Section: Discussionmentioning
confidence: 73%
“…20 The decrement in visual function reported by children with Ն Ϫ3.5 to Ͻ Ϫ2.5 D of myopia compared with those with refractive error Ն Ϫ0.5 D was 16.2 points, which exceeds the difference in self-reported visual function between persons with postoperative vision above and below 6/60 in the surgical eye in the above-cited study. This very significant impact of refractive error on self-reported visual function is consistent with our recent report of significant improvement in visual function with provision of spectacles among school-aged children having modest levels of refractive error in rural Mexico.…”
Section: Discussionmentioning
confidence: 73%
“…6), JUNE 2010 report suggests, supported by population-based studies in the area, 11 that many parents, teachers, and students in rural China advocate not correcting early or modest myopia in children in the belief that this will be healthier for the vision in the long term and has little effect on performance. However, data from children in this region demonstrate that significant deficits in visual function are found with even modest amounts of myopia, 20 and studies 28,29 have now shown that correction of even low myopia is associated with significant improvement in visual function. The amounts of refractive error going uncorrected in rural China are significant: in the Xichang Pediatric Refractive Error Study, 11 we reported a mean refractive error of −2.50 D and a median visual acuity less than 6/12 among myopic children not owning glasses and a mean refractive error of −3.00 D and a median visual acuity less than 6/15 among those owning but not wearing glasses.…”
Section: Commentmentioning
confidence: 99%
“…18 This finding exceeds the difference between adults with postoperative visual acuity above and below 6/60 in the operated-on eye after cataract surgery measured using an identical visual function instrument 19 in the same region. 20 Nevertheless, when a group of nearly 700 rural Chinese children were identified by screening as needing glasses, two-thirds failed to obtain them, including half those with habitual visual acuity of 6/18 or less, despite an educational intervention promoting glasses use targeted at parents, teachers, and children themselves. 21 The principal reason for failure to purchase glasses was lack of perceived need among 60% of children, whereas concerns about price were cited by only 16%.…”
mentioning
confidence: 99%
“…Uncorrected refractive error was the main cause (72.9%) of visual impairment in pseudophakic eyes in a study by Kandel and coworkers (9). In another study, 73.2% of cataract patients were within ± 1.0 D of the target refraction after surgery (10). A refractive accuracy (absolute deviation of target refraction from spherical equivalent) of ≤1 D was reported in 72%-97% of the patients and a total of 45%-80% of the patients showed a refractive accuracy of ≤0.5 D in different studies (11).…”
Section: Discussionmentioning
confidence: 99%